Religious Policy and Policizing Religion during the Tetrarchy - Gračanin, Hrvoje (2012)
The proposed paper endavours to survey and analyze main features of imperial intervention into religious affairs during the tetrarchy. Principal discussion will be centred around what was that motivated the tetrarchic rulers to initiate an openly intolerant and strongly coercive policy against the Christianity after several decades of relative calm, how this policy was implemented in different parts of the Empire, and what finally precipitated the profound change in which Christians and their religion were to be treated by official authorities, that is to say, in what manner, to what end and with what consequences the transition from hostility to tolerance to favoritism was effected. Special attention will be paid to the question to what degree the religion was viewed by the tetrarchic imperial governments as a mere tool for specific policy goals, and, on the other hand, how much emperors' personal religious persuasions or affinities might have influenced their respective policy-making. With regard to the attitude of imperial authorities towards religious issues, it will be contended that there was no real change between their perceived tolerance before and intolerance after Christianity had become the religio licita and the Christian values had been adopted and imposed by emperors as exclusively valid. In other words, the shift from polytheistic „tolerance“ - notwithstanding the fact that Christianity was not among religions enjoying such forbearance - to monotheistic „intolerance“ that happened was rather a matter of implementing the same political notions and governmental mechanisms to a newly created situation. Several other issues will also be addressed: how contemporary and later sources perceived the Diocletianic Persecution ; what degree of participation by the non-Christian ordinary people in the persecution can be determined from the sources ; and why there is no mention of the persecution in the works of non-Christian, late antique writers.
Projekt MZOS
ENG